The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1210/jcem-53-3-622
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hyperthyroidism with Sodium Ipodate (Oragrafin) in Addition to Propylthiouracil and Propranolol*

Abstract: Ten patients with hyperthyroidism due to Graves' disease were treated with sodium ipodate (1 g daily) in addition to propranolol (P) plus propylthiouracil (PTU; 100 mg every 8 h) and were compared with a control group of 8 patients treated with P and PTU. Patients on P and PTU had a mean (+/- SEM) basal free T3 index of 387 +/- 59 (normal, 70--160) compared with that of 409 +/- 47 (P greater than 0.05) in the sodium ipodate group. The respective basal free T4 index values (normal, 4.5-10.9) were 21.3 +/- 2.8 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…Ipodate or similar compounds have been found useful for short-term therapy of hyperthyroidism (16,17) and for special indications (18) but less effective for prolonged therapy (19). In our study, PTU plus ipodate gave the most profound decrease in serum T 3 with a decrease in the T 3 /T 4 % in serum to around one third of the initial value.…”
Section: Discussionmentioning
confidence: 48%
“…Ipodate or similar compounds have been found useful for short-term therapy of hyperthyroidism (16,17) and for special indications (18) but less effective for prolonged therapy (19). In our study, PTU plus ipodate gave the most profound decrease in serum T 3 with a decrease in the T 3 /T 4 % in serum to around one third of the initial value.…”
Section: Discussionmentioning
confidence: 48%
“…Basal and TRH-stimulated thyrotropin (TSH) values have been shown to increase or remain unchanged (2,(14)(15)(16)(22)(23)(24)(25)(26). In hyperthyroid subjects with Graves' disease, where there is increased expression of 59-MDI, T 4 levels decrease or remain unchanged (10,(27)(28)(29)(30)(31). In subacute thyroiditis, where there is uncontrolled release of thyroid hormones, and in euthyroid and hypothyroid subjects, serum T 4 levels increase or remain unchanged (2,12,15,16,25,26,32,33).…”
Section: Effects On Thyroid Hormone Physiologymentioning
confidence: 99%
“…Thirdly, as 500 mg of SI contains 308 mg iodine, large amounts of iodine are released during its metabolism, resulting in the inhibition of the organifica tion of iodine (Wolff-Chaikoff effect) [5] and of thyroid hormone release [6], Furthermore, SI seems to inhibit the hormonal secretion of the thyroid also by a direct effect which is independent of the inhibition induced by iodine [3,7,8]. It has been shown that during treatment with SI plasma T4 values decrease by 20-31 % in thyro toxic Graves' patients [1,[9][10][11][12][13], but remain unchanged or even rise in healthy adults [1,14,15]; on the other hand, plasma T3 values decrease by 67-76% in thyro toxic Graves' patients and by 25-55% in healthy adults [1,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%